Thursday, 14 June 2018 2018
DOI: 10.1136/annrheumdis-2018-eular.7187
|View full text |Cite
|
Sign up to set email alerts
|

THU0636 Canakinumab treatment in adult-onset still’s disease: case series

Abstract: BackgroundIn Adult-onset Still’s disease (AOSD), cases refractory to typical DMARDs, Canakinumab (an anti-IL-1ß monoclonal antibody) has been reported to be effective in a limited number of refractory cases.1 ObjectivesThe aim of this retrospective study was to represent AOSD patients treated with Canakinumab in 3 centres.MethodsThe follow up data of 10 AOSD patients (8 female, 2 male), who were followed up in outpatient clinics of 3 tertiary centres were reviewed retrospectively. The initial characteristics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Previous treatment with infliximab (n = 3), adalimumab (n = 2), and etanercept (n = 3) was observed in this study. 9 Patients in the studies by Vitale et al 5 (n = 9), Cavalli et al 7 (n = 4), Colafrancesco et al 8 (n = 4), Kougkas et al 22 (n = 1) did not experience any AEs during treatment with canakinumab.…”
Section: Canakinumabmentioning
confidence: 93%
See 2 more Smart Citations
“…Previous treatment with infliximab (n = 3), adalimumab (n = 2), and etanercept (n = 3) was observed in this study. 9 Patients in the studies by Vitale et al 5 (n = 9), Cavalli et al 7 (n = 4), Colafrancesco et al 8 (n = 4), Kougkas et al 22 (n = 1) did not experience any AEs during treatment with canakinumab.…”
Section: Canakinumabmentioning
confidence: 93%
“…At the time of analysis, six patients were on background corticosteroids up to 10 mg prednisolone/day maximum. 9 Colafrancesco et al identified four patients with AOSD, who switched from anakinra to canakinumab. After a mean duration of 22.1 months, the results were promising.…”
Section: Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…For the case series, 23 were judged to be at a low ROB 4,42-46,48-50,52,53,55-57,59,61-63,65,66,68-70 and 17 at a high ROB. 26,27,47,51,54,67,[71][72][73][74][75][76][77][78][79][80][81] Reporting was often not clear or complete. Ten of the case series showed high ROB in 1 or 2 fields, most commonly relating to poor or nonexistent reporting of patient baseline characteristics or outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…При БСВ, рефрактерной к предшествующей стандартной терапии НПВП, ГК, а также ингибиторами ФНОα, ИЛ6 и даже ИЛ1 (анакинра), опыт применения канакинумаба в целом весьма позитивен[45][46][47][48][49][50][51][52][53][54][55][56] (табл. 2).…”
unclassified